An Alternative Approach To Value / Price Theory - Hasan Gürak (Turkish Economic Association, 2004)
Modern economic science has become a grand parable, the study of a virtual economic world where the interactive robots engage in mechanical relationships. Although the natural sciences that initially inspired many economists has undergone drastic changes since Newton's era, modern economic science has grown up to become a castle of rigid conservatism. Theory of price, the backbone of all theories, is a typical example. This study is an alternative value-price theory, a labor embodied approach. The key concept of analysis is mental labor, the source of all value-added and accumulated, given natural resources and physical labor.
Keywords: D46; 330; Value; Price; Mental Labor; Labor; Exchange